NON-HYBRID ENSEMBLE SPATIAL REGRESSION ON HUMAN DEVELOPMENT INDEX (IPM) in CENTRAL JAVA: NON-HYBRID ENSEMBLE SPATIAL REGRESSION ON HUMAN DEVELOPMENT INDEX (IPM) in CENTRAL JAVA - Evi Ardiati Sazaen; Rochdi Wasono; Indah Manfaati Nur (Litbang PWM Jawa Tengah, 2020)
The human development index (HDI) is a measure to see an increase in regional development that has a very broad dimension, because it increases the quality of the population of an area in terms of life expectancy, education, and decent standard of living. In 2010 the Central Java HDI increased by 66.08% and increased by 4.44%, with the total HDI in 2017 of 70.52 percent. Spatial regression is the development of classical linear regression involving the region model. Spatial regression ensemble is a technique to be sent spasi spatial regression models by adding noise (additive noise). The type of spatial weighting used is Queen Contiguity. The selection of the best model using AIC and RMSE values. The purpose of this study is to provide an assessment of the distribution of HDI data in the Province of Central Java in 2017 and to do modeling using non-hybrid spatial ensemble regression regression. The results of this study are the SAR spatial method with ensemble giving results with AIC value of 143 and RMSE value of 1.3899 with a value of 90.09%. Significant variables on HDI are population density (X1), poverty (X2), school participation rates (X5), and average per capita per month for food and non-food (X7).